2019
DOI: 10.1108/er-04-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Job crafting and well-being in the elderly care sector: the effect of over-commitment

Abstract: Purpose The purpose of this paper is to analyze the moderation effect of over-commitment in the job crafting–well-being relationship, in the elderly care sector in Spain. Design/methodology/approach A cross-sectional design was implemented and a final sample of 353 participants were assessed using the Job Crafting Questionnaire, an adaptation of the Over-commitment Scale from the Effort-Reward Imbalance Questionnaire, and the General Health Questionnaire (GHQ-12). Findings A positive interaction between re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
(100 reference statements)
2
16
0
1
Order By: Relevance
“…Change initiatives using participatory approaches to managing change, where employees are involved as active agents has also been concluded as important for increasing success rates and reducing negative effects of organizational change (Abildgaard, Nielsen, & Sverke, 2018; Lundmark, von Thiele Schwarz, Hasson, Stenling, & Tafvelin, 2018). In eldercare settings, participatory job crafting activities, where employees drive change to elements of their job, has been concluded positively related to their well‐being (Romeo et al., 2019). Therefore, as there are no signs of the pace of organizational changes being reduced, paying more attention to how the they are managed seems warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Change initiatives using participatory approaches to managing change, where employees are involved as active agents has also been concluded as important for increasing success rates and reducing negative effects of organizational change (Abildgaard, Nielsen, & Sverke, 2018; Lundmark, von Thiele Schwarz, Hasson, Stenling, & Tafvelin, 2018). In eldercare settings, participatory job crafting activities, where employees drive change to elements of their job, has been concluded positively related to their well‐being (Romeo et al., 2019). Therefore, as there are no signs of the pace of organizational changes being reduced, paying more attention to how the they are managed seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Originally overcommitment was formulated as part of the effort-reward imbalance model and seen as a strategy to handle imbalance between effort and reward (Siegrist et al, 2004). However, overcommitment has also been studied as an independent coping strategy outside the effort-reward imbalance concept (Romeo, Yepes-Baldó, Piñeiro, Westerberg, & Nordin, 2019). Overcommitment is characterized by excessive job involvement and a desire to control a demanding situation and has been associated with a decrease in well-being and health among employees (Siegrist et al, 2004).…”
Section: Organizational Change and Employees' Overcommitmentmentioning
confidence: 99%
“…The JCQ scale is a 15-item instrument that includes three subscales: Cognitive Crafting (JCQ Cognitive; five items; for example, "How often do you remind yourself of the importance of your work for the broader community?" [α = 0.79, Romeo et al, 2019]); Task Crafting (JCQ Task; five items; for example, "How often do you change the scope or types of tasks that you complete at work?" [α = 0.79, Romeo et al, 2019]); and Relational Crafting (JCQ Relational; five items, such as "How often do you make friends with people at work who have similar skills or interests?"…”
Section: Job Craftingmentioning
confidence: 99%
“…[α = 0.79, Romeo et al, 2019]); Task Crafting (JCQ Task; five items; for example, "How often do you change the scope or types of tasks that you complete at work?" [α = 0.79, Romeo et al, 2019]); and Relational Crafting (JCQ Relational; five items, such as "How often do you make friends with people at work who have similar skills or interests?" [α = 0.71, Romeo et al, 2019]).…”
Section: Job Craftingmentioning
confidence: 99%
“…Recent studies have suggested that job crafting is widespread across a variety of occupations and that most employees have at least some latitude to sculpt the boundaries of their jobs (Zhang and Parker, 2019). Furthermore, job crafting may produce a number of positive effects, including employee subjective well-being, job satisfaction, organizational commitment, work engagement, job performance, and career success (Petrou et al , 2017; Romeo et al , 2019; Wang et al , 2018). In essence, the extant literature suggests that by crafting jobs, employees achieve a better fit between their jobs and themselves and inspire initiative in the workplace (Berg et al , 2013).…”
Section: Introductionmentioning
confidence: 99%